Effects of ulvan from enteromorpha intestinalis on the immunomodulatory activity of Penaeus vannamei and Penaeus monodon - Lauzon, Quenstein Dizon (College of Fisheries and Ocean Sciences, U. P. in the Visayas, 2015)
Disease outbreaks are constraints to aquaculture production affecting both the economic development of the country and the socio-economic status of shrimp farmers. Immunostimulants from seaweeds have gained increasing attention as a measure towards disease prevention. This study aimed to evaluate the effect of ulvan on the immunomodulatory activity of Penaeus vannamei and Penaeus monodon, specifically on total haemocyte count, respiratory burst activity, 0.07and phenoloxidase activity and resistance against White Spot Syndrome Virus. P. vannamei shrimps weighing 3.92 + 0.07 grams and P. monodon shripms weighing 3.54 + 0.14 grams used and fed with diets incorporated with different levels of ulvan inclusion (0.05%, 0.10%, and 0.15% kg-1 diet) and acontrol diet (0.00%) devoid of ulvan for 21 days. Shrimps were then challenged with White Spot Syndrome Virus. Hemolymp of healthy shrimps were extracted and used to measure for total haemocyte count, respiratory burst activity and phenolxidase activity. Results revealed that the virus-challenged shrimps fed with ulvan-incorporated diets exhibited prolonged survival than the control group. Immune response indices such as total haemocyte count, respiratory burst activity and phenoloxidase activity were significantly enhanced in shrimps fed diets containing ulvan than did those in the control group. Among the levels of ulvan tested, 0.05% inclusion level was enough to prolong survival as shown by the challenges tests for both penaeid shrimps. Estimated optimum dietary ulvan level by the quadratic model were 0.21% for P. vannamei and 0.15% for P. monodon. Results of the present study indicated that ulvan was an effective immunostimulant for P. vannamei and P. monodon especially against WSSV.